In vitro Activities of Nemonoxacin and Other Antimicrobial Agents Against Human Mycoplasma and Ureaplasmas Isolates and Their Defined Resistance Mechanisms - Wang, Na; Liu, Wancheng; Zhou, Yunheng; Liu, Yang (Frontiers in Microbiology, 2019)
Nemonoxacin, a newly developed non-fluorinated quinolone (NFQ), selectively inhibits bacterial DNA topoisomerase activity against bacteria. But Its activities against Mycoplasmas is rarely studied at present. Herein, the activities of nemonoxacin were evaluated against clinical isolates of Mycoplasma pneumoniae (M. pneumoniae), Mycoplasma hominis (M. hominis) and Ureaplasma species (Ureaplasma spp.) in comparison to fluoroquinolones, tetracyclines and macrolides. Nemonoxacin MICs (mg/ml) ranged from 0.03-0.25 for M. pneumoniae, 0.25-8 for M. hominis, 0.06->16 for Ureaplasma spp. obtained from infertility patients and 0.5-8 for Ureaplasma spp. from non-infertility, all of which are nearly comparable to fluoroquinolones. The activity of Nemonoxacin against Mycoplasmas was not affected by resistance to macrolides in the strains tested, but it seems to have the same resistance mechanism as fluoroquinolones. Minimum bactericidal concentrations (MBC) were within 2 dilutions of the MIC values, indicating a bactericidal effect. Nemonoxacin merits further study for treating infections caused by these organisms.